Efek Bekam terhadap Penurunan Nyeri Dismenore pada Mahasiswi - Yusro Hadi Maksum; Sri Lestariningsih; Septi Widiyanti (Jurnal Kesehatan Metro Sai Wawai, 2019)
Background: The prevalence of Indonesian women with dysmenorrhoea is estimated at 55% of women of childbearing age suffering from pain during menstruation. The most common dysmenorrhoea is reported in 60% -90% of adolescents. Purpose: To determine the effect of cupping on dysmenorrhea pain in students 2018. Methods: This study used a pre-experimental design with one group pretest and posttest design conducted in 2018. The study population was a student who experience severe pain or pain scale 7-9 (scale 0-10) with a minimum sample size of 32 people. The sampling technique uses consecutive sampling. The variable analyzed was the measurement of the respondent's disminore pain scale before and after cupping treatment. Data analysis by univariate analysis and bivariate analysis using paired samples T-test. Results: There was a difference in dismenore pain scale between before (6.78) and after cupping (5.09). Difference in pain 1.69 with p value 0,000. Conclusion: Cupping provides the effect or effect of reducing the pain scale on dysmenorrhea. Cupping can be one of the therapies or efforts that are recommended to deal with dysmenorrhoea pain disorders and free from the side effects of consuming chemical drugs.